Feeder automation and improved reliability for distribution systems - Nguyen, Hoang Viet; Nguyen, Van Ban (Journal of Technical Education Science, 2010)
This paper presents the feeder automation architectures and proposes a feeder automation system based on substation automation platform that can be applied to electrical distribution systems in Viet Nam to improve high economic-technical efficiency. The improved reliability is evaluated when applying feeder automation to distribution system in the Dak Nong province in fact also made. This solution can be applied to the rapidly increasing distribution system in Viet Nam to meet the current needs and future development.